STEM-Based Science E-Module: Is It Effective to Improve Students' Creative Thinking Skills? - Wulan Octi Pratiwi; Pramudiyanti Pramudiyanti; Ryzal Perdana (Universitas Lambung Mangkurat, 2024)
Elementary school students need to be able to think creatively, especially when facing various obstacles in their future careers. Therefore, it is necessary to develop STEM-based e-modules that can improve the creative thinking skills of elementary school students. This study aimed to describe how well STEM-based e-modules improved students' creative thinking skills about electrical energy. The subjects of this study were 30 students in sixth grade in MIN 2 Pringsewu, using the learning achievement test as a research instrument. Descriptive qualitative was used as the data analysis. The N-gain test was also used to evaluate the data. Based on the study's results, the electronic module was declared effective with an N-gain score of 0.7, which was determined from data analysis. Thus, it is assumed that e-modules based on the STEM approach were claimed to be able to develop students' creative thinking abilities further.